1992
DOI: 10.7326/0003-4819-117-11-891
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Hyponatremic Encephalopathy in Menstruant Women

Abstract: Women and men are equally likely to develop hyponatremia and hyponatremic encephalopathy after surgery. However, when hyponatremic encephalopathy develops, menstruant women are about 25 times more likely to die or have permanent brain damage compared with either men or postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
208
1
10

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 398 publications
(224 citation statements)
references
References 23 publications
5
208
1
10
Order By: Relevance
“…Postoperative hyponatraemia is a frequent and potentially dangerous complication in adults (Ayus et al, 1992), and is usually secondary to inappropriate hypotonic¯uid replacement, though plasma vasopressin concentration may also be increased in the postoperative period (Chung et al, 1986). Irrigation of the bladder with hypotonic glycine solutions during transurethral resection of the prostate can lead to direct absorption of water from the bladder into the venous circulation, producing dilutional hyponatraemia (Osborne et al, 1980).…”
Section: Euvolaemic Hyponatraemiamentioning
confidence: 99%
“…Postoperative hyponatraemia is a frequent and potentially dangerous complication in adults (Ayus et al, 1992), and is usually secondary to inappropriate hypotonic¯uid replacement, though plasma vasopressin concentration may also be increased in the postoperative period (Chung et al, 1986). Irrigation of the bladder with hypotonic glycine solutions during transurethral resection of the prostate can lead to direct absorption of water from the bladder into the venous circulation, producing dilutional hyponatraemia (Osborne et al, 1980).…”
Section: Euvolaemic Hyponatraemiamentioning
confidence: 99%
“…Among patients with hyponatremia, 1% develop encephalopathy, and of these, -20% die or suffer permanent brain damage (3,7). Death in such patients is largely the result of brain edema, which, if the brain is unable to adapt, often leads to cerebral herniation (3,7).…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33] Observational studies report variable occurrences of early postoperative hyponatremia, largely due to different surgical populations and serum [Na ? ] thresholds for defining hyponatremia.…”
Section: Iso-osmolar Hyponatremiamentioning
confidence: 99%
“…The implications are that women may have a greater tendency to retain free water in response to surgical stress. In a casecontrol study, Ayus et al 33 found that women and men are equally likely to develop hyponatremia and hyponatremic encephalopathy after surgery; however, menstruant women were 28 times more likely than men or postmenopausal women to die or to suffer permanent neurologic injury. There is speculation that estrogen and/or progesterone may facilitate brain cell adaptation to plasma hypotonicity and that decreased levels may interfere with the normal compensatory decreases in brain cell osmolality that occur in response to changes in extracellular tonicity.…”
Section: Iso-osmolar Hyponatremiamentioning
confidence: 99%
See 1 more Smart Citation